2013
DOI: 10.1177/1062860613508905
|View full text |Cite
|
Sign up to set email alerts
|

Using Health Literacy Guidelines to Improve Discharge Education and the Post-Hospital Transition

Abstract: The post-hospital transition represents a vulnerable period for patients discharged on new medications. Evidence-based discharge education may improve follow-up adherence and lower readmission rates. [1][2][3] Health literacy and health policy evidence should be considered when developing educational interventions. [4][5][6] Low health literacy is strongly associated with higher mortality. 5 We assessed the impact of a health education intervention on follow-up adherence and unplanned readmission among patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The evaluation of the chosen teaching strategy with respect to patient outcomes was discussed in 10 of these articles . Five studies identified increased or improved adherence to medication and treatment recommendations after specific interventions regarding delivery of information to patients . Five studies identified increased patient knowledge while one intervention demonstrated improved practical skills.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The evaluation of the chosen teaching strategy with respect to patient outcomes was discussed in 10 of these articles . Five studies identified increased or improved adherence to medication and treatment recommendations after specific interventions regarding delivery of information to patients . Five studies identified increased patient knowledge while one intervention demonstrated improved practical skills.…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles discussed conditions other than disorders of thrombosis and hemostasis while 5 articles identified approaches to generalized patient education . Eight articles discussed the education of health‐care providers with respect to the provision of patient education …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations